PENDAMPINGAN KELOMPOK WANITA TANI DALAM PEMANFAATAN SAMPAH ORGANIK RUMAH TANGGA MENJADI EKOENZIM DI DESA KAPUR, KABUPATEN KUBU RAYA, KALIMANTAN BARAT - Adwiyani, Pustika; Herwitarahman, Alifiya; Ningsih, Sulistia; Muliandari, Nadya; Annisa, Baaqy Amri; Ramadhani, Amelia Arum; Sitorus, Dermawati; Kusuma, Eka Widiawati Wijaya; Mahmudi, Mahmudi; Safriadi, Safriadi; Setiyadi, Wahyu; Gunadi, Gunadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
Organic waste contributed for 54.4% of the total volume of household waste. Household waste management and decomposition of organic waste that is not managed properly can cause environmental pollution. The management of organic waste into ecoenzymes is one of the efforts that can be made in overcoming household organic waste. The purpose of this activity is to increase partners' knowledge and skills in managing household organic waste as ecoenzymes. This community service activity was carried out in Kapur Village, Kubu Raya Regency, West Kalimantan, in January 2025. The materials used consisted of household organic waste, water, and brown sugar. This community service activity began with a basic knowledge test in the form of a pre-test, followed by presentations, demonstrations, and evaluations in the form of a post-test. The results showed a significant increase in the post-test results on all indicators assessed, compared to the pre-test results. So it can be concluded that there was an increase in participants' understanding and skills from 47.17% before training to 96.17% after training.